Charcot Arthropathy of the Foot and Ankle in Patients With Idiopathic Neuropathy. (October 2014) - Bariteau, Jason T.; Tenenbaum, Shay; Rabinovich, Alexander; Brodsky, James W.
Background: Charcot neuroarthropathy in the developed countries is primarily associated with diabetic neuropathy. This study investigated a series of patients with Charcot arthropathy associated with idiopathic peripheral neuropathy to evaluate the natural history in these patients and to evaluate the efficacy of a treatment protocol used for diabetic Charcot joints. Methods: The records and radiographs of patients with Charcot arthropathy of the foot and ankle treated between 1986 and 2009 were retrospectively reviewed. Patients with known causes of or risk factors for peripheral neuropathy were excluded, identifying 82 feet in 59 patients with idiopathic neuropathy. Twenty-three (39%) were bilateral. The average age was 76 years and the average follow-up was 60 months. Data were analyzed for medical history and diagnoses, medications, anatomic classification of Charcot arthropathy, history of ulcerations, ambulatory status, shoe wear and bracing, and operative interventions. Patient care was based on previous published treatment algorithms, based on conservative management with operative intervention reserved for nonhealing ulcers, infection, and/or nonplantigrade, unbraceable feet. Therapeutic success was a plantigrade foot with healed soft tissue envelope that allowed weight-bearing. Results: In all, 55% involved the midfoot (type 1), 34% the hindfoot (type 2), and 11% the ankle, (type 3A). Seventy-one of 82 feet were successfully treated at the time of last follow-up. Thirty-six feet (43%) were treated nonoperatively with success in 33 (92%). Forty-six of 82 feet required operative intervention, with success at last follow-up in 38 (83%). There were 8 operative failures resulting in 2 transtibial amputations and 6 feet with persistent ulceration. Conclusions: This series of patients with Charcot arthropathy associated with idiopathic neuropathy demonstrated a wider spectrum of Charcot arthropathy of the foot and ankle than has been previously recognized or documented. At the present time, heightened awareness is needed to promote accurate diagnosis and appropriate treatment in nondiabetic patients with Charcot arthropathy. Level of Evidence: Level IV, retrospective case series.